Claim-making under India’s Mahatma Gandhi National Rural Employment Guarantee Act (MGNREGA): Barriers and opportunities for women’s voice and agency over asset selection - Kosec, Katrina; Kyle, Jordan; Narayanan, Sudha; Raghunathan, Kalyani; Ray, Soumyajit (International Food Policy Research Institute, 2024)
This paper examines the dynamics of women's claim-making within the Mahatma Gandhi National Rural Employment Guarantee Act (MGNREGA) scheme in India, focusing on their participation in selecting durable assets for climate resilience. Despite legal entitlements and protections for women within the program, gender disparities persist in claiming public resources. Utilizing a mixed-methods approach including surveys and qualitative interviews, the study uncovers various pathways to women’s claim-making, influenced by factors such as gender norms around mobility and women’s voice and agency, internal barriers and constraints including comfort in public speaking, and knowledge of the program and its various procedures for selecting assets. While challenges to women’s effective participation remain, findings from our analysis suggest potential for interventions to reduce gender gaps and enhance inclusivity in planning processes. Moreover, the study underscores the importance of recognizing diverse claim-making pathways to promote inclusion effectively within the program.